PENGABDIAN MASYARAKAT MELALUI KEGIATAN BAKTI SOSIAL DI DESA PASAKA KECAMATAN SABBANGPARU KABUPATEN WAJO - Yuniarti, A.; Nurwana, Andi; Jamaluddin, Andi (Arunika: Jurnal Pengabdian Masyarakat, 2022)
Community service in the form of social services carried out by a team of lecturers provides tremendous benefits to the Pasaka Village Community, Sabbangparu District, These activities are in the form of socializing the prevention of underage marriage, maternal and child health counseling, drug counseling. The purpose of this activity is to provide health services to the community for the realization of public welfare in the health sector as well as increase the sense of social care among fellow human beings. The activity has been carried out since 05,10 & 11 August 2022 by involving the Head of the Women's Protection and fulfillment of children's rights DINSOSP2KBP3A Wajo Regency and medical personnel, such as sub-district midwives coordinators and nurses and attended by 90 participants, consisting of 25 people to prevent child marriage. , Maternal and child health counseling as many as 30 people and drug counseling at SMPN 3 Sabbangparu as many as 35 people